Real-time on line tuning of fuzzy controller for two link rigid-flexible robot manipulators - Marwan A.; Nagi F.; Sahari K.; Hanim S. (2023)
In this paper, a real time self-tuning MIMO fuzzy bang-bang controller (FBBC) is proposed to control two link rigid and flexible robot manipulators. Two link rigid and flexible robot manipulators are highly nonlinear plants. The fuzzy control is based on the Takagi-Sugeno's type architecture fuzzy model combined with online self-tuning so that both the desired transient and steady state responses can be achieved. The online self-tuning is based on the gradient steepest descent tuning method, which learns to tune the FBBC, "s inputs and outputs gains online. The controller operation is demonstrated by simulation of tracking ability and manipulator's positioning control with different payload. Based on the simulation results, the proposed controller shows good performance in tracking ability even with big payload.